COMMUNITY EMPOWERMENT BY THE TOURISM OFFICE IN THE DEVELOPMENT OF SADE TOURISM VILLAGE, CENTRAL LOMBOK REGENCY, WEST NUSA TENGGARA PROVINCE - Azzura, Anastasya Nur; Mulyana, Mulyana (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2024)
West Nusa Tenggara Province has a lot of tourism potential and attracts tourists. This research aims to describe and analyze community empowerment in the development of Sade Tourism Village in Rembitan Village, Pujut District, Central Lombok Regency. The research method uses qualitative and data collection techniques, such as interviews, observation, and documentation. Data analysis techniques use reduction, data presentation, and research conclusions. The informants were determined using a purposive sampling technique. Researchers used the operationalization of community empowerment from Mardikanto & Soebianto (2013). The results show that the human development dimension needs to be more specific, and human resource development is not provided for people living around Sade Village. The business development dimension shows that community participation is very high in maintaining infrastructure and keeping Sade Tourism Village beautiful. At the same time, in terms of promotion, some still need to understand the importance of promotional activities. The environmental development dimension shows that the people of Sade Village are very concerned about the cleanliness and comfort of the environment for tourists. The institutional development dimension indicates that Pokdarwis supports community empowerment activities in Sade Village. In conclusion, community empowerment carried out by the Central Lombok Regency Tourism and Culture Office in developing the Sade Tourism Village has been carried out quite well. Keywords: Tourism Village, Community Empowerment, Tourism Village Development.